2005
DOI: 10.1016/j.jtcvs.2005.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal dysfunction after the Norwood procedure

Abstract: After a Norwood procedure, swallowing dysfunction occurs in 48% of patients, with aspiration in 24%, and results in increased length of hospital stay. Left recurrent laryngeal nerve injury, seen in 9% of patients, is an uncommon cause of swallowing dysfunction. Postoperative aspiration generally resolves over time, whereas vocal fold paralysis does not. Systematic evaluation of swallowing function allows appropriate tailoring of feeding regimens and might contribute to decreased hospital and interstage mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
208
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(216 citation statements)
references
References 22 publications
8
208
0
Order By: Relevance
“…Totally 50 reported were collected, including 19 (38%) case reports or case series [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], 1 (2%) technique [30], 17 (34%) retrospective [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 13 (26%) prospective reports [7,11,[49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Totally 50 reported were collected, including 19 (38%) case reports or case series [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], 1 (2%) technique [30], 17 (34%) retrospective [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 13 (26%) prospective reports [7,11,[49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…Is has been reported that the prevalence of left vocal cord paralysis after PDA ligation was 4.2% of the whole patient population, and it was 8.0% in infants with low birth weights [32]. The intraoperative damage to the left recurrent laryngeal nerve along its course around the PDA during the dissection of the nerve might result in stretch injury [55]. Røksund et al [11] found that infants with left vocal cord paralysis had a lower birth weight, longer duration of ventilation, and the greater proportion with bronchopulmonary dysplasia.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Management of these cases includes thickening feeds to nectar or honey consistency, feeding positioning (right side down), and/or supplemental/sole tube feeding [26,[28][29][30][31][32][33][34][35].…”
Section: Nutrition Management Of Complications and Comorbiditiesmentioning
confidence: 99%
“…Nutrition measures to be considered in these cases are: fl uid restriction, concentrated formula caloric density or parenteral nutrition, using formulas low in electrolytes, and in case of dialysis -supplement with water soluble vitamins and trace elements, providing 2-3 g/kg/day protein for continuous renal replacement therapy and 4 g/kg/day for peritoneal dialysis [26,[28][29][30][31][32][33][34][35].…”
Section: Nutrition Management Of Complications and Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation